Characterization of AQPs in Mouse, Rat, and Human Colon and Their Selective Regulation by Bile Acids - Yde, Jonathan; Keely, Stephen; Wu, Qi; Borg, Johan F.; Lajczak, Natalia; O’Dwyer, Aoife; Dalsgaard, Peter; Fenton, Robert A.; Moeller, Hanne B. (Frontiers in Nutrition, 2016)
In normal individuals, the epithelium of the colon absorbs 1.5-2 L of water a day to generate dehydrated feces. However, in the condition of bile acid malabsorption (BAM), an excess of bile acids in the colon results in diarrhea. Several studies have attempted to address the mechanisms contributing to BAM induced by various bile acids. However, none have addressed a potential dysregulation of aquaporin water channels, which are responsible for the majority of transcellular water transport in epithelial cells, as a contributing factor to the onset of diarrhea and the pathogenesis of BAM. In this study we aimed to systematically analyze the expression of AQPs in colonic epithelia from rat, mouse and human and determine whether their expression is altered in a rat model of BAM. Mass spectrometry-based proteomics, RT-PCR, and western blotting identified various AQPs in isolated colonic epithelial cells from rats (AQP1, 3, 4, 7, 8) and mice (AQP1, 4, 8). Several AQPs were also detected in human colon (AQP1, 3, 4, 7-9). Immunohistochemistry localized AQP1 to the apical plasma membrane of epithelial cells in the bottom of the crypts, whereas AQP3 (rat, human) and AQP4 (mice, human) were localized predominantly in the basolateral plasma membrane. AQP8 was localized intracellularly and at the apical plasma membrane of epithelial cells. Rats fed sodium cholate for 72 h had significantly increased fecal water content, suggesting development of BAM associated diarrhea. Colonic epithelial cells isolated from this model had significantly altered levels of AQP3, 7, and 8, suggesting that these AQPs may be involved in the pathogenesis of bile acid induced diarrhea.